PENGARUH TERAPI RENDAM KAKI DENGAN AIR HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA IBU HAMIL DENGAN HIPERTENSI DI KLINIK PRATAMA MADINA KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG TAHUN 2024 - Amirah, Nada; Rahmawati, Rahmawati (Jurnal Penelitian Kesmasy, 2025)
Pregnant hypertension is indicated by two or more values ​​of 140/90 mmHg. If untreated, common pregnancy-related hypertension, including preeclampsia and eclampsia, can result in the mother losing consciousness and developing catastrophic heart failure, kidney failure, or a brain hemorrhage. The Deli Serdang Regency's Percut Sei Tuan District served as the site of the 2024 inquiry. This was the field in which the study was conducted. The purpose of this study was to investigate whether or not pregnant women with high blood pressure may benefit from soaking their feet in warm water to reduce their blood pressure. Both the pre- and post-tests were provided to the study participants, and the same group of people took both of the examinations. A pretest and posttest were administered prior to and subsequent to therapy. The research employed numbers like an experiment. Women with high blood pressure who were pregnant before and after warm water foot soaks had a value of 0.0001. The fact that it is less than alpha indicates that the value that is relevant is lower. At the Pratama Madina Clinic in the Percut Sei Tuan District of the Deli Serdang Regency in the year 2024, pregnant women who were experiencing high blood pressure were able to enjoy a reduction in their blood pressure by soaking their feet in warm water. It seems that Ha is correct, but H0 is correct. Keywords: Pregnant, Hypertension, Therapy